Acanthus ilicifolius Leaf Extract Potential as an Alternative Functional Food Beverage - Wulansari, Nadya Treesna; Padmiswari, A.A Istri Mas; Harditya, Kadek Buja; Sintyadewi, Putu Rima (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
This study aimed to identify the active compounds, antioxidants, and antibacterial effectiveness of Acanthus ilicifolius leaves against microbial food-borne diseases as an alternative to functional food beverages. This study was an experimental study using a completely randomized design on a laboratory-scale experiment (in vitro), and the data obtained in this study were analyzed by analysis of variance (ANOVA). The results showed that the phytochemical screening of Acanthus ilicifolius leaves contained metabolite compounds of flavonoids, phenols, and tannins of 1072.44 mg/100g, 2619.64 mg/100 g, and 3205.66 mg/100g, respectively. The IC50 value of Acanthus ilicifolius leaf extract, namely 221.67 ppm, has fragile antioxidant activity. At the same time, the highest inhibition was produced at an extract concentration of 100%. The concentration of Acanthus ilicifolius leaf extract at a concentration of 100% resulted in the highest average inhibition on bacteria of 9.67 ± 0.36 mm and 10.12 ± 1.12 mm, respectively, against Staphylococcus aureus, Escherichia coli, and Salmonella sp. of 6.82 ± 0.15 mm, 6.18 ± 0.02 mm, and 6.19 ± 0.07 mm.